'How do you say it in Arabic, in Hebrew, in English?' Towards a better understanding of children's agentic behaviour in novel language learning. Issue 7 (9th August 2021) - Schwartz, Mila; Deeb, Inas; Hijazy, Sujoud
ABSTRACT: The aim of this study was to explore patterns of children's agency enactment in second-language learning as reflected in their language learning and social interactions in a bilingual Arabic–Hebrew-speaking classroom. We examined the connection between these behaviour patterns and the children's L2 progress in the bilingual classroom. The study used purposive sampling to select five information-rich cases that were representative of the bilingual classroom population. We performed two year-long ethnographic observations of the children whom we chose to participate in the study and collected testimonies from their parents and teachers to enhance credibility. The analysis revealed the following three patterns of language-based agentic behaviour: enthusiastic behaviour; unwilling behaviour, and fluctuating behaviour. The enthusiastic pattern was easy to observe because two children, who were identified as proactive L2 learners, tended to integrate socially with native L2-speaking peers and made considerable progress in L2. In our analysis of the unwilling and fluctuating patterns, we relied more on triangulating our observations with the teachers' and parents' input. An implication of this study for educators is the importance of thinking about how to increase enthusiasm for L2 learning among children who either show reluctance or lack self-confidence in L2 use in peer communication.